Assessment of teeth elemental content using μ‐EDXRF: effects by in‐office and at‐home bleaching products. (20th October 2014) - Silveira, J.; Godinho, J.; Mata, A.; Carvalho, M. L.; Pessanha, S.
<x xml:space="preserve">Abstract</x> The purpose of this in vitro study is to assess whether the elemental content of tooth enamel is altered when bleaching the teeth with bleaching gel. Because of tooth bleaching growing popularity and to match the public demands, manufacturers increased the range of bleaching products available, changing its presentation, techniques and concentration of active principles. This way, two different bleaching products were compared, one for in‐office and another for domestic use. In order to perform this evaluation, sound vestibular surfaces of anterior healthy teeth, extracted for periodontal or orthodontic reasons, were treated with the bleaching products accordingly to manufacturer instructions. Spectra were acquired using the M4 Tornado μ‐XRF setup, and quantitative calculations were performed using fundamental parameter method to determine the elemental composition of the analyzed samples before and after treatment. No significant statistical differences in the mineral content of the analyzed teeth were obtained. Copyright © 2014 John Wiley & Sons, Ltd.